APPLICATION OF ONLINE LEARNING ON ACID-BASE TITRATION TOPIC TO IMPROVE STUDENTS’ LEARNING INTEREST - Dinda Syiseni; Ade Ismayani; Rusman Rusman (FKIP USK, 2022)
Students' interest in learning chemistry, especially in acid-base titration material during the pandemic, makes the learning process ineffective, students tend to be quiet and not interested in learning. The application of learning that can be used during a pandemic is online learning. This study aims to measure students' interest in learning through the application of online learning and to describe student learning activities and student reactions to the application of online learning. The type of research used is quantitative research with quasi-experimental methods and the One Group Posttest-Only Design. This research was conducted at SMA Negeri 1 Banda Aceh with 28 students in class XI MIA 4 taking samples using purposive sampling technique. Collecting data through observation sheets of learning activities and student learning interest questionnaires. The output of the study showed that there were learning activities in the good category with an average value of 90% and 93% observed by the observer. The application of online learning can be used during the current pandemic, seen from the responses of students in the good category with an average score of 76.67. The level of student interest in learning before the application of online learning was 65.71%, after the application of online learning obtained very good results of 77.08%. N-Gain score obtained 32.51 which is included in the medium category. Based on the results of the study, it can be concluded that the application of online learning can increase students' interest in learning.Keywords: Online, interest in Learning, Google Classroom, Acid-Base Titration